In the beginning of linguogeography of the Middle Volga Region: scientific contribution of professor E.S. Skoblikova (on the 100th anniversary of the Samara scientist) - T. E. Bazhenova (Вестник Самарского университета: История, педагогика, филология)
The article assesses the scientific contribution of a prominent representative of the Samara Linguistic School, Professor of Samara State University Elena Sergeevna Skoblikova to the study of the dialects of the Middle Volga region. Her passion for dialectology provided her with her first successful steps into big science and remained throughout her subsequent scientific activity. For many years, she was a participant and organizer of dialectological expeditions to study the dialects of Penza, Ulyanovsk, Samara and Orenburg regions. In the late 1940-ies, even before the appearance of generalizing works on linguistic geography, E.S. Skoblikova in her Ph.D. thesis described the patterns in the geographical distribution of the features of dialectal forms of personal pronouns in the dialects of the vast territory of the European part of Russia. A number of her articles highlight the functioning and history of formation of the features of dialectal vocalism, which are important from the point of view of the typology of the Volga dialects. In the works of E.S. Skoblikova, the basis for the classification of Middle Russian dialects and methods for determining the genesis of secondary dialects is laid, taking into account linguogeographical data on phonetic and morphological features. Her scientific research in dialectology is characterized by attention to the synchrony and diachrony of linguistic processes in dialects, the study of individual links of dialect systems in connection with the system of the Russian language as a whole. The results of E.S. Skoblikova's dialectological research contributed to the clarification of the regional picture of the dialect landscape in the Middle Volga region. The attempt to analyze the scientific heritage of E.S. Skoblikova is interesting and significant both in terms of linguistic historiography and in terms of analyzing the achievements of regional dialectology and the entire Russian linguogeography.